Imitation perfection : A simple Rule to prevent discrimination in procurement - Mass,Helene. et al. (American Economic Journal Microeconomics)
Procurement regulation aimed at curbing discrimination requires equal treatment of sellers. However, Deb and Pai (2017) show that such regulation imposes virtually no restrictions on the ability to discriminate. We propose a simple rule$1 (Bimitation perfection$1 (Bthat restricts discrimination significantly. It ensures that in every equilibrium, bidders with the same valuation distribution and the same valuation earn the same expected utility. If all bidders are homogeneous, revenue and social surplus optimal auctions consistent with imitation perfection exist. For heterogeneous bidders, however, it is incompatible with revenue and social surplus optimization. Thus, a trade-off between non-discrimination and optimality exists. - Reproduced s